Performance of Guinea Grass in Relation to Fertility and Cutting Management under Rainfed Conditions - Ram, S N; Trivedi, B K (Annals of Arid Zone, 2016)
A field experiment was conducted during July 2007 to June 2010 on sandy loam soil at Central Research Farm of Indian Grassland and Fodder Research Institute, Jhansi, to find out the effect of nitrogen, farmyard manure and cutting intervals on growth, forage productivity and quality of Guinea grass (Panicum maximum Jacq.) under semi-arid rainfed conditions. Harvesting of Guinea grass at 60 day interval along with application of 80 kg N ha-1 in combination with 5 t FYM ha-1 recorded significantly higher dry forage yield (6.15, 11.30 and 7.82 t ha-1) 40 and 60 day harvest intervals + lower levels of fertility and at par with 60 days harvest intervals + 40 kg N ha-1 + 10 t FYM ha-1 and 60 days harvest intervals + 80 kg N ha-1 + 10 t FYM ha-1. Dry forage yield of Guinea grass recorded during first, second and third years were 4.25, 8.61 and 5.22 t ha-1, respectively. Harvesting at 40 day interval recorded significantly higher crude protein at and lower NDF and ADF contents than at 60 days interval. Key words: Cutting interval, farmyard manure, forage yield, nitrogen levels, Panicum maximum